DESKRIPSI SIKAP MAHASISWA PEROKOK DI FAKULTAS X SEMARANG TERHADAP PERINGATAN KESEHATAN PADA BUNGKUS ROKOK - Ririh Prayogi (Jurnal Kesehatan Masyarakat (Undip), 2015)
Smoking trend among students aged 15-19 years in Indonesia has increased 3 times from 7,1% to 43,3%. By looking atincreasingthe number of smokerswhoactuallyIndonesiangovernmenthas setregulation toaddress the problem ofsmoking. In 2013, Indonesian Governmentissued DecreeNo.28of 2013The Inclusion of andHealthWarning and InformationonTobaccoProductPackaging. Picture healthwarningis one of thegovernment's effortstoprotect publicfromnegativeeffects ofsmoking.Studentshavestrongidealismthattheyhave different attitudefrom theapplication of thePHW. EconomicsandBusiness Faculty, Diponegoro Universuty is one of college that hasstudentwith atendencyof smoking behavior which is getting betteralthoughithas receivededucational assistancefrom tobacco companies. The purposeof studyis describe about the attitude ofsmoker studentinthe x facultySemarangtohealthwarningson cigarette pack. This type of researchisdescriptivequantitativemethodwithcross-sectional study. Samplesare taken from 100 respondentswithnon-probability sampling. Data were analyzed usingunivariatedata analysis. The results showed59%of respondentshavegoodknowledge aboutnegativeeffects ofsmoking, 78% of respondentshave good attitudetowards picture healthwarningson cigarette packs, 73% of respondentshave good attitudetowards about no smoking area regulation, and53% of respondentshave good perceptionabout support of familyand peers.